Effect of health educational intervention on early detection of sickle cell disease among adolescent population in tribal areas of East Singhbhum district, Jharkhand: A study protocol - Sarbasree Bhattacharjee; Jarina Begum; Ranjitha S. Shetty; Syed Irfan Ali; Ravi Ranjhan Jha; Anit Kujur; Mohd Amir Ansari (PLoS ONE, 2026)
Sickle Cell Disease (SCD) remains a public health challenge in India, particularly among tribal populations. Gaps persist in early detection, awareness, and culturally appropriate interventions, especially among adolescents, a key target group for long-term prevention. The study aims to evaluate the effect of a school-based educational intervention on the awareness, attitude, and early detection of SCD among adolescents in tribal and non-tribal areas of East Singhbhum district, Jharkhand. A sequential explanatory mixed-methods design will be used. In the quantitative phase, adolescents aged 13–19 years from selected government schools will undergo baseline and follow-up assessments of knowledge and attitudes using structured questionnaires. A health education session will be delivered, followed by screening for anemia and SCD using hemoglobin estimation and the solubility test. In the qualitative phase, in-depth interviews with stakeholders, including healthcare providers, ASHAs, school staff, caregivers, and affected adolescents, will explore perceptions, barriers, and feedback related to the SCD and National Sickle Cell Anemia Elimination Mission, 2023 implementation. A quasi-experimental one-group pretest-posttest was conducted among 41 adolescents (13–15 years) from a government school. Knowledge scores increased from 5.31 ± 2.87 to 12.57 ± 2.09 (mean difference: 7.26, 95% CI: 6.10–8.42, p < 0.001). Attitude scores from 1.44 ± 9.21 to 55.83 ± 8.42 (mean difference: 54.39, 95% CI: 50.89–57.89, p < 0.001). Willingness to undergo SCD testing rose from 37% to 83% post-intervention. Stakeholder feedback indicated high acceptability and enthusiasm for similar sessions. The study will provide critical insights into the effectiveness of adolescent-focused health education in enhancing SCD awareness and screening uptake. It will also highlight disparities between tribal and non- tribal populations and inform policy-level recommendations for targeted, equitable interventions. This research will address gaps in adolescents’ SCD awareness and early detection, contributing to the national goal of SCD elimination through evidence-based, community-embedded strategies. Clinical Trial Registry of India: CTRI/2024/12/078542